Integrated Marketing Communication Dalam Meningkatkan Brand Awareness Pada Bisnis Startup Di Grosirone - Putri, Syifa Amalia; Sartika, Ika (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
This research examines the implementation of Integrated Marketing Communication (IMC) in enhancing brand awareness at GrosirOne, a startup company operating in the fast-moving consumer goods (FMCG) e-commerce sector. The study is motivated by the increasing competition among startups and the importance of building strong brand awareness, especially in the traditional market segment. This research uses a descriptive qualitative method with data collection techniques such as interviews, observations, and literature review, involving GrosirOne staff and merchant partners who play a key role in the company's operations. The findings reveal that GrosirOne applies five elements of integrated marketing communication: advertising, sales promotion, public relations, personal selling, and direct marketing. These elements are not implemented separately but are well-coordinated to support the company's primary goal of building stronger brand awareness. The study concludes that IMC plays a crucial role in building brand awareness and boosting sales. To achieve more significant results, the company needs to implement more intensive educational strategies and a more personal approach to both consumers and partners. This research provides an important contribution as a guideline for startups to strengthen their brand using integrated communication strategies. Not only will this enhance brand awareness, but it will also help improve overall sales.